Cultural transmission and correlational selection in Late Period projectile points from the Puna of Salta, Argentina (AD 900 - 1500) - Varde, Maria (2018)
This work proposes a methodology for documenting metric patterns of trait correlation in Late Period (ca. AD 900-1500) projectile points from the Puna and pre-Puna of Salta, Argentina. In so doing, our main goal is to explain the patterns observed in terms of mechanisms of cultural evolution and selection. We apply this methodology to assemblages from four archaeological sites whose chronologies are well established. As a result, we were able to document low degrees of variation, as well as high co-variation between metrical traits, suggesting a process of correlational selection that preserved an artefact design with a structure of highly integrated traits. This lends support to the hypothesis where replication of these projectile points ocurred within a process of stabilizing cultural selection through biased transmission mechanisms, which in turn favoured the selection of artefacts suitable for effective weapons.